Associations of dietary patterns and abdominal obesity in the adult population. Results of the Russian epidemiological ESSE-RF study - N. S. Karamnova; S. A. Shalnova; A. I. Rytova; O. B. Shvabskaya; Yu. K. Makarova; Yu. A. Balanova; S. E. Evstifeeva; A. E. Imaeva; A. V. Kapustina; G. A. Muromtseva; S. A. Maksimov; E. B. Yarovaya; et al. (Российский кардиологический журнал)
Abdominal obesity (AO) is an alimentary-dependent risk factor, the development and prognosis of which is directly specified by eating habits.Aim. To study the associations of dietary patterns and AO among the adult Russian population.Material and methods. The analysis was carried out using representative samples of male and female population aged 25-64 years (n=19297; men, 7342; women, 11,955) from 13 Russian regions. The response was about 80%. Nutrition was assessed based on the prevalence of consumption of the main food groups forming the daily diet. Results are presented as odds ratios and 95% confidence intervals.Results. Men with AO, compared with men without AO, more often consume red meat and vegetables/fruits daily by 12% and 13%, respectively, as well as less often eat cereals and pasta, confectionery, sour cream, and cottage cheese by 17%, 24%, 14%, and 19%, respectively. In women with AO, compared to women without AO, there are more differences in the diet, as they more often daily consume red meat by 28%, fish and seafood by 26%, poultry by 23%, meat and sausages and fruits/vegetables by 14%, milk, kefir, yogurt by 11%, as well as less often — cereals and pasta, sweets, and sour cream by 11%, 14%, and 8%, respectively. In women with AO, the prevalence and amount of drinking beer and dry wines is lower, but they consume spirits more frequently (p=0,0001), but without significant differences in amount. Men with AO have a higher prevalence and amount of drinking dry and fortified wines, as well as strong alcoholic drinks. Men with AO drinks higher amount of beer. In addition, men with AO showed a positive association with alcohol consumption (χ=53,64, p<0,0001), while women with AO had a negative association (χ=28,64, p<0,0001). Cardioprotective eating habits are more often (17%) present among people with AO without sex differences.Conclusion. The study revealed significant differences in dietary patterns of persons with AO compared with those without AO, most pronounced in women.